IKLAN MOBIL PADA SURAT KABAR HARIAN SINGGALANG EDISI OKTOBER 2012 : KAJIAN SEMIOTIKA - Elsa Adel Pertiwi; Novia Juita; Abdurahman Abdurahman (Jurnal Bahasa dan Sastra, 2013)
The purpose of this study was to describe (1) markers and markers in car advertisements in daily newspapers Singgalang October 2012 issue, and (2) the meaning of car advertisements in daily newspapers Singgalang October 2012 issue. The data of this study were car ads on daily newspaper edition Singgalang October 2012. Data analysis techniques of research is done by inventory data through daily newspapers Singgalang October 2012 issue, and then classify the data by grouping based on the theory that the next set, the data were analyzed by grouping data and mengiinterpretasikan by way of interpretation and restrictions based on a theoretical framework, and analyze data and discussion to draw conclusions. The findings of this study are semiotic signs in form of markers (signifier) and twenty-sign (signified) and twenty meanings contained in automobile advertisements on newspapers Singgalang October 2012 issue.   Kata kunci :    Iklan, Surat Kabar, Semiotika.